The roads to disaster, or rewriting history from the margins—Yū Miri's JR Ueno Station Park Exit. Issue 2 (3rd July 2019) - Iwata-Weickgenannt, Kristina
ABSTRACT: In Ruth Ozeki's words, 3.11/Fukushima represents a "rift in time", which not only split an imagined temporal continuum into before and after, but makes the before appear in a different light. In the present article, Yū Miri's JR Ueno-eki kōenguchi is read as a literary response to, and expression of, this perceptual shift. Yū's focus on an exploited migrant worker from rural Fukushima who spends his last years as a homeless in the capital chimes in with the post-3.11 discourse about the subordinate position of Northern Japan within the Japanese nation-state. The novel can thus be interpreted as a palimpsestic corrective; a critical rewriting of Japan's post-war history from the viewpoint of those whose existence has been marginalized, if not completely erased from collective memory. To illustrate this point, the analysis focuses on Yū's deconstruction of the myth surrounding the 1964 Tokyo Olympics (an implicit criticism of the upcoming post-nuclear 2020 Olympics), as well as her provocative juxtaposition of a homeless and the Japanese imperial family. It is argued that by problematizing historical memory and forgetting, discursive visibility and invisibility, Yū not only intertwines various narrative threads, but also manages to re-connect the before and after the disaster in a new, critical way.